Manajemen Arsip Elektronik pada Unit Penerimaan Mahasiswa Baru Universitas Cokroaminoto Palopo - Syafriadi, Syafriadi; Kurniadi, Wisnu; Ilyas, Muhammad (Department of Electrical Engineering, University of Patria Artha, 2022)
This research aims to implement a digital archive management system in the admission unit of new students of cokroaminoto palopo University which is expected to be one of the solutions in an effort to emphasize the obstacles faced in archive management that result in the difficulty of searching for new student archives caused by the accumulation of archives or archives that are not managed with a good storage system, the loss of archives,Â and as an effort to utilize technology, archive management requires a system that is used to facilitate archive management. Systems that are no longer conventional but have utilized technology that uses electronic media based on the use of computers. The object of the research is the New Student Admission Unit of Cokroaminoto Palopo University and the type of research conducted by the author is a type of development research or Research and Development (R&D). This research aims to develop an archive system at the New Student Admission Unit of Cokroaminoto Palopo University. Electronic archival system in the New Student Admission unit of Cokroaminoto Palopo University must be supported by the use of electronic archival system devices, namely hardware and software. The hardware used is a set of computers, scanners, UPS, and software used, namely website-based applications with intranet and internet networks. Processes in electronic archival systems include scanning processes, editing processes and storage processes.